PENGETAHUAN TENTANG LINGKUNGAN HIDUP, KEPEDULIAN LINGKUNGAN DAN ETOS KERJA DENGAN PARTISIPASI KERYAWAN DALAM MENDUKUNG PROGRAM LINGKUGAN KESEHATAN DAN KESELAMATAN KERJA (LK3) DI PT ENGGAL SUKSES PERKASA BEKASI – JAWA BARAT - M . Kosasih (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2016)
The objective of this research is to study the relationship between the employee’s knowledge of environment, their careness for environment, and their work ethics in the process of supporting the Environment Health and Safety program at PT Enggal Sukses Perkasa. This company, which is located in Bekasi, West Java, is Astra Group’s industrial manufacture subcontractor which has participated in Small-Medium Entrepreneurs-Astra Green Company (SME’s-AGC) training conducted by Yayasan Dharma Bhakti Astra.This research applies survey method, by combining two forms of questionnaires: test and non-test. The result of this research shows that: The employee’s knowledge of environment has a positive and significant relation with the employee’s roles in supporting the Environment Health & Safety program, the employee’s careness for environment has a positive and significant relation with the employee’s roles in supporting the Environment Health & Safety program, the employee’s work ethics has also a positive and significant relation with employee’s roles in supporting Environment Health & Safety program. The employee’s knowledge of environment, their careness for environment, and their work ethics, all together have a positive and significant relationship with employee’s roles in supporting the Environment Health & Safety program. Therefore, it can be assumed that the more knowledge of environment, the more careness that employees has for environment, and their work ethics, the more participative they will be in supporting the Environment Health& Safety program in their company.